2008
DOI: 10.1080/10474410802269164
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Assessment, Consultation, and Intervention Practices: Urban School Psychologists' Use, Importance, and Competence Ratings

Abstract: This article examines the practices of school psychologists who work within an urban school district. Participants (N D 86) rated 20 specific practices on their current use, their importance, and their level of competence. Overall the school psychologists rated their involvement in traditional assessment activities as significantly more common than consultation/collaboration and prevention/ intervention; however, they indicated consultation and prevention/intervention activities as significantly more valued th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Several studies have shown that school psychologists spend the majority of their time involved in assessment activities, especially as they relate to special education eligibility determinations (Stoiber & Vanderwood, 2008). However, it is not identified as the most valuable activity or the area where professional development was desired (Stoiber & Vanderwood, 2008). Although assessment and special education procedures are necessary roles, their continued dominance has prevented school psychologists from taking on a broader continuum of SMH services (Harrison et al, 2004;Meyers & Swerdlik, 2003).…”
Section: Time and Personal Prioritizationmentioning
confidence: 99%
“…Several studies have shown that school psychologists spend the majority of their time involved in assessment activities, especially as they relate to special education eligibility determinations (Stoiber & Vanderwood, 2008). However, it is not identified as the most valuable activity or the area where professional development was desired (Stoiber & Vanderwood, 2008). Although assessment and special education procedures are necessary roles, their continued dominance has prevented school psychologists from taking on a broader continuum of SMH services (Harrison et al, 2004;Meyers & Swerdlik, 2003).…”
Section: Time and Personal Prioritizationmentioning
confidence: 99%
“…In addition to the lack of diversity in the field, there is a nationwide shortage of school psychology faculty members. The growth in the public school population, especially when considered in light of the increasing diversity of student backgrounds and the increasing number of students identified for special education services, has contributed to changes in personnel needs for all education professions, including school psychology (Stoiber & Vanderwood, 2008). The need for additional school psychologists to fill vacant and newly created positions in public schools has been a persistent problem since the mid-1980s (see Curtis et al, 2004, for full projections of the shortage).…”
Section: National Shortage Of School Psychologistsmentioning
confidence: 99%
“…Teachers report feeling ill‐equipped to meet the needs of children who are disruptive and indicate being frustrated in their attempts to develop safe and nurturing classroom environments (Gettinger, Stoiber, Goetz, & Caspe, 1999). The fact that teachers need more support in the area of effectively managing children's challenging behavior is further supported by a recent study indicating that school psychologists reported classroom‐based behavioral interventions as their greatest need area for professional development (Stoiber & Vanderwood, 2008).…”
mentioning
confidence: 94%